Misi Profetik dan Efektivitas Dakwah dalam Perjanjian Hudaibiyah - Nunung Khoiriyah (Buletin Al-Turas, 2010)
Several approaches can be used to gain the objective of dakwah, which is to meet the human nature with religion or to make someone realizes the truth of Islam and finally practices it This realization which is constructed by giving a dear thinking space, a dean heart, and with no violence is essential in creating successful dakwah. It is historically proved by prophet Muhammad PBUH through the Hudaibiyyah Agreement: 1) conflict-free condition is a conducive situation to spread Islam outside the Arabic Peninsula; 2) recognition of Islam as a legitimate religion in the Arab community, enabling an open dialogue about Islam; 3) acknowledgment of Muslim existence in Arab community; 4) by promoting peace, Muslims open free access to perform religious practices such as hajj and umrah in the following years.